Kedudukan Hukum Akta Notaris dihadapan para Penghadap berkaitan dengan Hak Nasabah Perbankan - Lia Azrina (Universitas Medan Area, 2021)
This study aims to determine the position of the notary deed that is not read out in front of the parties and to explain the legal consequences, namely in the form of sanctions and to find out what factors cause the notary not to read the notary deed before the deed is signed by the parties. The research method used is empirical legal research methods. The results show that notaries in accordance with the applicable laws have the obligation to read out the notary deed in front of the parties before the deed is signed and legalized to ensure that the notary deed has perfect evidentiary power. The factor that causes deeds not to be read out by the notary is because to save time and the deed is read out by the notary's staff. In conclusion, the notarial deed which is not read out in front of the parties remains binding on the parties stated in the deed, but if in the future problems such as default, the power of proof of the deed may become under-the-hand power and / or null and void in accordance with a court decision. Reading deeds via video conference might be a discourse to make it easier for notaries to fulfill the increasing need for authentic deeds, even though reading deeds via video conference is impossible to carry out considering the signing of the deed must be done immediately after reading the notary deed in front of the parties by the notary public